Reducing Sexual Orientation Discrimination: Experimental Evidence from Basic Information Treatments. (5th December 2022) - Aksoy, Cevat Giray; Carpenter, Christopher S.; De Haas, Ralph; Dolls, Mathias; Windsteiger, Lisa
Abstract: We study basic information treatments regarding sexual orientation using randomized experiments in three countries with strong and widespread anti‐gay attitudes: Serbia, Turkey, and Ukraine. Participants who received information about the economic costs to society of sexual orientation discrimination were significantly more likely than those in a control group to support equal employment opportunities based on sexual orientation. Information that the World Health Organization (WHO) does not regard homosexuality as a mental illness increased social acceptance of sexual minorities, but only for those who reported trust in the WHO. Our results have important implications for policymakers aiming to expand the rights of lesbian, gay, and bisexual people worldwide.